The Need For Etiquette Reflected In Suzanne Enoch's England's Perfect Hero Novel (2004): A Sociological Approach - Dewi., Anindya Nurul Kusuma; , Dr. M. Thoyibi, M.S; , Titis Setyabudi, S.S. M. Hum (2014)
This study is about the need for etiquette in England at the nineteenth century in England's Perfect Hero novel using sociological approach. The objectives of this study are to identify by the structural elements of the novel and to analyze the novel based on the sociological approach. This study is qualitative research. There are two data sources: primary and secondary. The primary data source is England's Perfect Hero novel by Suzanne Enoch released in 2004. The secondary data sources are other sources taken from books, dictionary and internet that supported to the analysis. The technique of the data collection is library research with the steps are reading repeatedly the novel, determining the character, underlying the important parts, classifying and determining the relevant data, taking notes from the material and other sources. The technique of the data analysis is descriptive analysis. The result of study comes to the following conclusions. Firstly, based on the structural analysis, England's Perfect Hero describes the lack of etiquette in English men, it causes the women create several etiquettes to make man act as gentleman. Secondly, based on sociological analysis, there is a close relationship between the story of the novel and the reality of English society in the twenty first century, in which some people ignore the importance of etiquette in social interaction.